Modeling HEDLA magnetic field generation experiments on laser facilities - Fatenejad, M; Bell, A; Benuzzi-Mounaix, A; Crowston, R; Drake, R; Flocke, N; Gregori, G; Koenig, M; Krauland, C; Lamb, D; Lee, D; Marques, JR; et al. (2013)
The Flash Center is engaged in a collaboration to simulate laser driven experiments aimed at understanding the generation and amplification of cosmological magnetic fields using the FLASH code. In these experiments a laser illuminates a solid plastic or graphite target launching an asymmetric blast wave into a chamber which contains either Helium or Argon at millibar pressures. Induction coils placed several centimeters away from the target detect large scale magnetic fields on the order of tens to hundreds of Gauss. The time dependence of the magnetic field is consistent with generation via the Biermann battery mechanism near the blast wave. Attempts to perform simulations of these experiments using the FLASH code have uncovered previously unreported numerical difficulties in modeling the Biermann battery mechanism near shock waves which can lead to the production of large non-physical magnetic fields. We report on these difficulties and offer a potential solution. © 2012 Elsevier B.V.